They Never Left: Drivers of Memory of Dictatorship and Impressions of Ferdinand E. Marcos as President After February 1986 - Tigno, Jorge V. (Archīum Ateneo, 2024)
Between 1972 and 1986, Ferdinand E. Marcos of the Philippines headed an autocratic system that allowed him to rule with little to no accountability. Some 36 years after FM (as he is popularly called) and family were driven from power into exile in Hawaii, his son, Ferdinand ‘Bongbong’ Marcos, Jr., was overwhelmingly elected President in the May 2022 general elections. This turnaround seemed puzzling to many, but others saw a long-term deliberate process of rehabilitation after the family returned to the Philippines. Our paper explores how Filipinos remembered FM in the years after his ouster. What drives the memory of dictatorship in the Philippines? Using time series data on public opinion about FM post-ouster, we find that a generally positive appreciation of Marcos as former president had crystallised early on across nearly all the major variables of age, sex, education, location and ethnicity.